The Global and Indonesian Landscape on Child Vaccination, Immunization, and Gender - Pahruroji, Pahruroji; Virgianita, Asra (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2024)
This article discusses the complex dynamics of vaccination, child immunization, and gender within the global and Indonesian landscapes. It highlights the intricate relationship between policies, cultural norms, economic conditions, and social challenges that influence vaccination status and access to immunization services. The study employs a literature review approach to examine various sources, including international frameworks, government policies, and scientific research, to explore the intersectionality of gender and immunization in Indonesia. Findings from this article underscore the crucial role of gender in shaping vaccination status and access to immunization services, particularly in Indonesia, where disparities persist despite efforts by the government and international aid organizations. Recommendations included aiming to achieve vaccination goals. Recommendations include improving data collection, implementing gender-responsive policies, combating misinformation, strengthening healthcare systems, promoting community engagement, and empowering women and fathers to actively participate in healthcare decision-making and immunization advocacy, ultimately aiming to achieve vaccination goals.